The complete mitochondrial genome sequence of Stichopus variegatus (Echinodermata: Holothuroidea) and phylogenetic studies of Echinodermata - Yang, Qiuhua (Mitochondrial DNA B Resour, 2019)
At present, there exist some confusing issues on the species classification and phylogeny in Echinodermata. In this study, we first determined and described the complete mitochondrial genome of Stichopus variegatus. The complete mitogenome sequence had a circular mapping molecular with the total length of 16,315 bp and contained 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a putative control region. To further validate the newly determined sequences, phylogenetic trees involving all the Holothuroidea and other Echinodermata species available in GenBank Database were constructed. These results would be used for the species identification and further phylogenetic studies of Echinodermata.